2010
DOI: 10.1177/0022219409355483
|View full text |Cite
|
Sign up to set email alerts
|

Stereotypes of Individuals With Learning Disabilities: Views of College Students With and Without Learning Disabilities

Abstract: To explore possible reasons for low self-identification rates among undergraduates with learning disabilities (LD), we asked students (38 with LD, 100 without LD) attending two large, public, research-intensive universities to respond to a questionnaire designed to assess stereotypes about individuals with LD and conceptions of ability. Responses were coded into six categories of stereotypes about LD (low intelligence, compensation possible, process deficit, nonspecific insurmountable condition, working the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 46 publications
(61 reference statements)
0
68
1
2
Order By: Relevance
“…Such stereotypes are difficult to challenge as they are not perceived by the general population as harmful, but rather as benign. As a consequence, the internalisation of stereotypical attitudes towards people with intellectual disability may result in barriers to self‐expression (May & Stone ; McCarthy ).…”
Section: Main Themesmentioning
confidence: 99%
“…Such stereotypes are difficult to challenge as they are not perceived by the general population as harmful, but rather as benign. As a consequence, the internalisation of stereotypical attitudes towards people with intellectual disability may result in barriers to self‐expression (May & Stone ; McCarthy ).…”
Section: Main Themesmentioning
confidence: 99%
“…Within this general growing group of students with LD, pre-service teachers with LD are a unique subgroup of students, from an academic point of view (see Wertheim, Vogel, & Brulle, 1998) as well as in terms of emotional traits (May & Stone, 2010). The goal of the present study was to examine how pre-service teachers with LD perceive their professional training during their first years of Teacher College and whether perception will change during the course of the first term of their undergraduate studies.…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted by May and Stone (2010) revealed that students with learning disabilities believed peers would view their intellectual abilities as less than average if their disability were disclosed. As well, these students believed their peers would perceive the use of accommodations as cheating.…”
Section: Enrollmentmentioning
confidence: 99%